Analysis of Postoperative Complications and Related Factors Affecting Prognosis in 50 Patients with Distal Radius Fractures. (15th October 2021) - Yuan, Kun; Wang, Fei; Lu, Hongjian
Abstract : Objective . To explore the postoperative complications of distal radius fractures and analyze the related factors that affect its prognosis. Methods . The clinical data of 50 patients with distal radius fractures admitted to our hospital from October 2016 to September 2019 were retrospectively analyzed. All patients were followed up for 6–12 months, and their postoperative complications were recorded. Collect general patient information and related clinical data. During the follow-up process, Gartland and Werley wrist function scoring system was used to evaluate the prognosis of patients' joint function. Univariate analysis and multiple logistic regression models were used to analyze the related factors that affected the prognosis of patients. Results . 15 patients with postoperative complications were found during the follow-up period, with an incidence rate of 30.00%. Univariate analysis showed that the patient's age, cause of injury, AO classification, shortened deformity, whether it was osteoporosis, surgical method, whether it was combined with other fractures on the same side, whether it was comminuted fracture, and the time to start postoperative exercise were all related to the distal radius. The prognosis of fractures is related (P < 0.05 ). Multivariate logistic analysis showed that age, AO classification, surgical method, whether it was combined with other fractures on the same side, whether it was comminuted fracture, and the time to start postoperative exercise were the independent factors affecting the prognosis of distal radius fractures (P < 0.05 ). Conclusion . The postoperative complications of distal radius fractures are higher. The prognosis is related to the patient's age, AO classification, surgical method, whether it is combined with other fractures on the same side, whether it is comminuted fracture, and the time to start postoperative exercise. Therefore, choosing an appropriate surgical method and starting exercise in time can effectively improve the recovery of the patient's wrist function and reduce the occurrence of complications.